Improving Children's Fine Motor Skills through Meronce Activities in Kindergarten - Sulemi Sulemi; Vivid Dratis R.; Dwi Agusti S.; Mujiatiningsih Mujiatiningsih (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2022)
This study aimed to determine the improvement of fine motor skills through Meronce Activities in Aisyiyah Mamajang Kindergarten, Makassar City. The research conducted in this research is a collaborative participation class action. At the same time, the population in this study is group B Aisyiyah Mamajang Kindergarten Makassar City, and the sample in this study amounted to 15 students. Data were collected using observation sheets. Then the data were analyzed using descriptive analysis. The survey results after the action were carried out in Cycle I; as many as six children, or 40% of the 15 children, received the criteria for developing according to expectations in the aspect of students' speed in carrying out Meronce activities. Regarding accuracy, four children obtained the category of developing as expected, or 27%. After taking action in Cycle II, there was an increase from 15 students who received the criteria for designing according to expectations, six people in the speed aspect, and nine children in the category of developing very well in the speed aspect or 100%. For the accuracy aspect, seven students got the developing as expected, and eight children got the developing very well or 100%. In Cycle II, the child has reached the indicator of success, so the research is stopped.